2008
DOI: 10.1053/j.gastro.2008.07.009
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Pharmacogenetic Trial of Sibutramine on Weight Loss and Body Composition in Obese or Overweight Adults

Abstract: Background/ Aim-Weight loss in response to sibutramine is highly variable. We assessed the association of specific markers of polymorphisms of candidate a2A adrenoreceptor, 5-HT transporter and GNβ3 genes and weight loss with sibutramine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
1
37
1
Order By: Relevance
“…In addition, previous studies (Grudell et al 2008;Hauner et al 2003;Hsiao et al 2009) in pharmacogenetics suggested that the GNB3 rs5443 SNP could influence weight reduction and body composition change under sibutramine therapy. The observation of Grudell et al (2008) and Hsiao et al (2009) in their studies showed that the GNB3 TT/TC genotypes were associated with greater weight loss with the sibutramine group than with the placebo group.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In addition, previous studies (Grudell et al 2008;Hauner et al 2003;Hsiao et al 2009) in pharmacogenetics suggested that the GNB3 rs5443 SNP could influence weight reduction and body composition change under sibutramine therapy. The observation of Grudell et al (2008) and Hsiao et al (2009) in their studies showed that the GNB3 TT/TC genotypes were associated with greater weight loss with the sibutramine group than with the placebo group.…”
Section: Discussionmentioning
confidence: 96%
“…The observation of Grudell et al (2008) and Hsiao et al (2009) in their studies showed that the GNB3 TT/TC genotypes were associated with greater weight loss with the sibutramine group than with the placebo group. In contrast to Grudell et al (2008) and Hsiao et al's (2009) studies, a report by Hauner et al (2003) indicated that individuals with the GNB3 CC genotype were associated with more weight loss from sibutramine administration. In addition, Grudell et al's (2008) analyses were consistent with Hsiao et al's (2009) results that treatment with sibutramine resulted in significantly greater reduction in body fat for specific GNB3 TC/TT genotypes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…19,49,50 Preliminary findings suggest that specific genes might modulate the response to sibutramine treatment. [51][52][53] In 149 obese women, the GG and AA genotypes of the phenylethanolamine N-methyltransferase gene (the ratelimiting enzyme in catecholamine biosynthesis) were associated with greater weight loss with sibutramine than the AG genotype. 51 Another study in 111 patients reported that the GNβ3 CC genotype predicted 5% weight loss with sibutramine.…”
Section: Studies Assessing the Weight-lowering Potential Of Sibutraminementioning
confidence: 99%